PERBEDAAN KADAR EKSKRESI YODIUM URIN (EYU), KONSUMSI GARAM BERYODIUM, DAN TINGGI BADAN ANAK BARU SEKOLAH (TBABS) (Studi di Daerah Replete dan Non-replete GAKY Kabupaten Magelang) - Putri Tiara Nur Mahardika; Suyatno Suyatno; Apoina Kartini (Jurnal Kesehatan Masyarakat (Undip), 2019)
One of the fundamental factors causing Iodine Deficiency Disorders (IDD) is low environmental iodine, so that people who depend on local food will have iodine deficiency. In Magelang Regency there is a replete area, specifically areas that have a history of IDD problems in the past and have been intervened, so the problem can be overcome. This study aimed to analyze differences in UIE levels, consumption of iodized salt, and height of children in replete and non-replete area of IDD, Magelang Regency. This analytic observational study was conducted with cross-sectional design for 60 children in the first grade Bandongan 1 Elementary School which in replete area and Blondo 3 Elementary School which in non-replete area. Data collected includes: characteristics of respondents, consumption of iodized salt, type and quality of salt, UIE levels, height, and nutrient intake (energy, protein, and iodine). Analysis of this study using independent t-test and mann-whitney test. The median of children UIE level in replete area was 200,5 μg/L, while non-replete area was 212,5 μg/L. The average consumption of iodized salt in replete area was 3,09 g/day and non-replete area was 4,81 g/day. The average of height for age were -0,79 for replete area and -0,22 for non-replete area. This results showed that there weren’t differences between UIE levels, parent’s height, level of nutritional adequacy (energy, protein, and iodine) in replete and non-replete area of IDD (p>0,05). This results showed that consumption of iodized salt and child’s height in replete was lower than non-replete area of IDD and difference was significant (p<0,05).